"You never know who are Sami or speak Sami" Clinicians' experiences with language-appropriate care to Sami-speaking patients in outpatient mental health clinics in Northern Norway. Issue 1 (1st January 2016) - Dagsvold, Inger; Møllersen, Snefrid; Stordahl, Vigdis
Abstract : Background: The Indigenous population in Norway, the Sami, have a statutory right to speak and be spoken to in the Sami language when receiving health services. There is, however, limited knowledge about how clinicians deal with this in clinical practice. This study explores how clinicians deal with language-appropriate care with Sami-speaking patients in specialist mental health services. Objectives: This study aims to explore how clinicians identify and respond to Sami patients' language data, as well as how they experience provision of therapy to Sami-speaking patients in outpatient mental health clinics in Sami language administrative districts. Method: Data were collected using qualitative method, through individual interviews with 20 therapists working in outpatient mental health clinics serving Sami populations in northern Norway. A thematic analysis inspired by systematic text reduction was employed. Findings: Two themes were identified: (a) identification of Sami patients' language data and (b) experiences with provision of therapy to Sami-speaking patients. Conclusion: Findings indicate that clinicians are not aware of patients' language needs prior to admission and that they deal with identification of language data and offer of language-appropriate care ad hoc when patients arrive. Sami-speaking participants reported always offering language choice and found more profound understanding of patients' experiences when Sami language was used. Whatever language Sami-speaking patients may choose, they are found to switch between languages during therapy. Most non-Sami-speaking participants reported offering Sami-speaking services, but the patients chose to speak Norwegian. However, a few of the participants maintained language awareness and could identify language needs despite a patient's refusal to speak Sami in therapy. Finally, some non-Sami-speaking participants were satisfied if they understood what the patients were saying. They left it to patients to address language problems, only to discover patients' complaints in retrospect. Consequently, language-appropriate care depends on individual clinicians' language assessment and offering of language choice.